Young children's museum geographies: spatial, material and bodily ways of knowing. Issue 5 (3rd September 2018) - Hackett, Abigail; Holmes, Rachel; MacRae, Christina; Procter, Lisa
ABSTRACT: In this guest editorial, we outline a new field of children's museum geographies. We do this by opening up a space for the reader to engage with a collection of papers that trace embodiment, tacit and emplaced knowing, material entanglements and non-representational aspects of experience in accounts of children's presence in museums. We hope that this special issue will act as an impetus for further working, thinking and collaborating, firstly by disrupting the conflation of children in museums with narrowing notions such as learning and talk, and secondly by highlighting the rich potential of museums as a space of interest for the field of children's geographies.